Evaluation of the pediatric post anesthesia discharge scoring system in an ambulatory surgery unit. Issue 6 (8th January 2015) - Moncel, Jean Benoit; Nardi, Nicolas; Wodey, Eric; Pouvreau, Aline; Ecoffey, Claude; Lerman, Jerrold
Summary Introduction To optimize the care pathway for children scheduled for ambulatory surgery, a pediatric postanesthetic discharge scoring system (Ped‐PADSS) was developed from a score used in adults. The objective of this study was to evaluate this score prospectively on a cohort of children who had a day case surgical procedure. Materials and methods This was a single center prospective observational study. Inclusion criteria were predefined as follows: children aged 6 months–16 years at the time of the study, with a scheduled day surgery. Discharge was validated by Ped‐PADSS scores ≥9, obtained at one hour intervals, after the return from the operating room and with the agreement of the surgeon. The duration of postoperative hospitalization was compared with data collected before the implementation of the score using the Student's t‐test. Results From February to July 2012, 1060 children were included. One hour after the return from the operating room, 97.2% of children were dischargeable using Ped‐PADSS. Two hours after the return from the operating room, 99.8% of children were dischargeable. The median postoperative hospital stay (n = 1041) was reduced by 69 min compared to the median stay before using the output score (n = 150) (P < 0.01). Conclusion The Ped‐PADSS score allows for the majority of children to be discharged 1 h after their return from the postanesthesia care unit. Children who were discharged using the Ped‐PADSS score returned home in safe and optimal conditions.